Degree of virtuality, intragroup conflict, emotional regulation of team members and group performance: What relations? - Santos, Susana Loureiro dos (2018)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação